Device-based methods in facial skin restoration during rehabilitation after plastic and reconstructive surgeries - Hutchenko, K.S.; Shevchuk , O.S.; Savitska, A.O.; Kozachuk, V.L.; Alotaibi, S.R.; Shevchuk, S.V. (Medicni Perspektivi, 2025)
An analysis of current scientific literature shows that device-based treatment methods play an important role in the comprehensive postoperative rehabilitation of patients after reconstructive and plastic surgery on the face. Despite the active introduction of radiofrequency, laser, ultrasound and light methods into clinical practice, the question of comparing their effectiveness remains open. This is particularly relevant in the treatment of the consequences of deep mechanical and thermal damage, which are accompanied by complex processes of skin restoration. Objective: to conduct an analysis, including a multidimensional comparative analysis, of device-based methods for facial skin restoration during rehabilitation after plastic and reconstructive surgery. The study involved 72 subjects (women and men, average age 40.5±8.1 years) who underwent plastic or reconstructive surgery on the face. Depending on the method of hardware exposure, patients were divided into four groups: radiofrequency, laser, ultrasound (HIFU) and light (LED/IPL) therapy. The control group (n=24) consisted of patients who received only traditional treatment without device-based methods. The Vancouver Scar Scale (VSS), biometric parameters (Cutometer®, Corneometer®), dermatoscopy and the visual analogue scale (VAS) were used to evaluate the results. A multidimensional comparative analysis was performed using the sum of squares method, which took into account five key characteristics: clinical effectiveness, duration of the procedure, number of sessions, interval between surgery and the start of therapy, and cost of treatment. LED light therapy received the highest rating (R=1), which was characterised by the shortest interval between surgery and the start of treatment (21 days), the lowest cost (6,000 UAH) and the shortest duration of the procedure (0.5 hours). Radiofrequency and non-ablative laser therapies received the same rating (R=2), indicating their high effectiveness but longer and more expensive therapy (1 hour and 9-15 thousand UAH, respectively). The ultrasound method ranked third (R=3) due to significant time (90 days) and financial (15,000 UAH) constraints, as well as the duration of the procedure (1.5 hours). The results of the study indicate the advisability of early inclusion of LED and radiofrequency therapy in standardised rehabilitation protocols to improve skin healing quality, reduce the risk of scarring and enhance the overall aesthetic effect after plastic and reconstructive surgery on the face.